Total thoracoscopic combined lingulectomy and pericardial cystectomy - Zhang, Yi; Lin, Yong; Shen, Guoyi; Li, Guilong (Journal of Thoracic Disease, 2014)
Thoracoscopic anatomic segmentectomy is usually more complex than lobectomy. This video shows a 58-year-old female who suffered from limited bronchiectasis of the lingular segment of the left upper lung and a pericardial cyst on the same side. Both of these benign thoracic diseases can cause pleural adhesions. Repeated chronic inflammation contributes to hypervascularity and lymph node enlargement, making surgery more difficult. We used single-direction thoracoscopic segmentectomy via a three-port approach and successfully removed the lingula and pericardial cyst.